In Vitro Evaluation of Ruminal Fermentation and Methane Production in Response to the Addition of Modified Nano-Bentonite with or Without Saccharomyces cerevisiae to a Forage-Based Diet - Sohila Abo-Sherif; Sobhy Sallam; Ali M. Allam; Mounir El-Adawy; Yosra Soltan (Animals)
Modified nano-clays, alone or combined with probiotics, may offer a novel and sustainable approach to improve ruminal fermentation and mitigate CH4 emissions in high-fiber diets. This study evaluated the properties and effects of modified nano-bentonite (MNB), with or without yeast (Saccharomyces cerevisiae), compared to natural bentonite (NB) and monensin, using the in vitro gas production (GP) technique. The substrate used was a basal diet composed primarily of forage (Trifolium alexandrinum clover) in a 70:30 forage-to-concentrate ratio. The treatments were a control group receiving the basal diet without additives; a monensin-added diet containing 40 mg/kg of dry matter (DM); a yeast-added diet with Saccharomyces cerevisiae at 2 × 108 CFU/g of DM; a NB clay-added diet at 5 g/kg of DM; and MNB diets added at two levels (0.5 g/kg of DM (MNBLow) and 1 g/kg of DM (MNBHigh)), with or without S. cerevisiae. MNB showed a smaller particle size and improved properties, such as higher conductivity, surface area, and cation exchange capacity, than NB. Sulfur and related functional groups were detected only in MNB. No differences were observed in total GP, while both the monensin diet and the MNBHigh-with-yeast diet significantly reduced CH4 emissions compared to the control (p < 0.05). The MNBHigh-without-yeast combination significantly (p < 0.05) reduced hemicellulose degradation, as well as total protozoal counts, including Isotricha and Epidinium spp. (p < 0.05), compared to the control. Ammonia levels did not differ significantly among treatments, while NB and MNBHigh diets tended to have (p = 0.063) the highest short-chain fatty acid (SCFA) concentrations. These findings suggest the potential modulatory effects of yeast and MNB on rumen fermentation dynamics and CH4 mitigation.